Iron redox effect on the structure and viscosity of a sodium silicate glass and melt - Sukenaga, Sohei; Cicconi, Maria Rita; Yamada, Hiroki; Wakihara, Toru; Ohara, Koji; Shibata, Hiroyuki; Neuville, Daniel R. (Journal of Chemical Physics, 2024)
The viscosity of silicate melts is one of the most important physical properties for understanding high-temperature phenomena in magmatic systems and material processing. The effects of composition and temperature on viscosity have long been elucidated. Although iron ions are the main components of magmatic systems, their influence on viscosity remains unclear because the behavior of iron is complicated; iron ions have two redox states, Fe3+ and Fe2+. Here, we elucidate the viscosity of an iron-sodium-silicate system with a variety of iron redox states at temperatures close to its glass transition temperature (Tg). The redox states and structures of the samples were characterized using x-ray absorption near-edge structure (XANES) spectroscopy, Raman spectroscopy, synchrotron x-ray total scattering, and density (molar volume) measurements. The viscosity increased (by more than four orders of magnitude) with an increase in the ratio of Fe3+ to total Fe (Fe3+/Fetot), whereas the temperature dependence of the viscosity was larger for glasses with a higher Fe3+/Fetot ratio at temperatures close to the glass transition temperature. The tendencies in viscosity and structural variation against the Fe3+/Fetot ratio support the consensus on the structural roles of Fe3+ and Fe2+ from previous studies: Fe3+ ions have a stronger tendency to behave as network formers than Fe2+ ions.
CRIS-Team Scopus Importer:2025-02-04